Novel parasitic chytrids infecting snow algae in an alpine snow ecosystem in Japan - Nakanishi, Hiroaki; Seto, Kensuke; Takeuchi, Nozomu; Kagami, Maiko (Frontiers in Microbiology, 2023)
Microbial communities are important components of glacier and snowpack ecosystems that influence biogeochemical cycles and snow/ice melt. Recent environmental DNA surveys have revealed that chytrids dominate the fungal communities in polar and alpine snowpacks. These could be parasitic chytrids that infect snow algae as observed microscopically. However, the diversity and phylogenetic position of parasitic chytrids has not been identified due to difficulties in establishing their culture and subsequent DNA sequencing. In this study, we aimed to identify the phylogenetic positions of chytrids infecting the snow algae, Chloromonas spp., bloomed on snowpacks in Japan. By linking a microscopically picked single fungal sporangium on a snow algal cell to a subsequent sequence of ribosomal marker genes, we identified three novel lineages with distinct morphologies. All the three lineages belonged to Mesochytriales, located within “Snow Clade 1”, a novel clade consisting of uncultured chytrids from snow-covered environments worldwide. Additionally, putative resting spores of chytrids attached to snow algal cells were observed. This suggests that chytrids may survive as resting stage in soil after snowmelt. Our study highlights the potential importance of parasitic chytrids that infect snow algal communities.